Quantum‐Dot‐in‐Polymer Composites via Advanced Surface Engineering. Issue 9 (9th August 2017) - Lesyuk, Rostyslav; Cai, Bin; Reuter, Uta; Gaponik, Nikolai; Popovych, Dmytro; Lesnyak, Vladimir
Abstract : A straightforward approach to the fabrication of quantum‐dot (QD)‐in‐polymer solid composites with a tunable content of the nanoparticles is presented. This procedure includes the colloidal synthesis of QDs based on CuInS2 with their subsequent shelling with ZnS and ligand exchange with two molecules containing monomer units. These QDs, on the one hand, retain their bright photoluminescence after the exchange. On the other hand, their functionalized surface bears double‐bond‐containing groups that are copolymerizable with common monomers such as styrene and methyl methacrylate via free radical polymerization. The composites possess an enhanced photostability, in particular polystyrene‐based solids, being tested in a focus of a powerful irradiation. During this treatment, an interesting light‐soaking effect consisting in a significant enhancement of the photoluminescence is observed. Owing to their superior stability under the light irradiation, these composites are very promising for application in low‐cost solar‐energy devices such as photovoltaic windows, solar concentrators, spectral converters. Perspectives of the practical application of the composites are well supported by Monte Carlo simulations. The developed method of surface engineering can be applied to a wide range of other QDs to incorporate them into a polymer matrix and fabricate highly transparent and stable composites. Abstract : CuInS2 quantum‐dot‐in‐polymer composites are fabricated by a straightforward approach including ligand exchange with molecules containing monomer units and subsequent copolymerization with styrene. The composites possess an enhanced photostability under powerful light irradiation owing to the light‐soaking effect. They are very promising for application in low‐cost solar‐energy devices, such as photovoltaic windows, solar concentrators, and spectral converters.